Formulation and evaluation of taste masking sachets containing quetiapine fumarate - A, Abhilash; T, Malyadri; Ch, Saibabu (Journal of Innovations in Applied Pharmaceutical Science (JIAPS), 2021)
Quetiapine fumarate is a tetracyclic piperazino-azepine antidepressant agent. It is given with a dose of 15-45mg orally once a day. The absorption of this drug is rapid and complete. Due to first pass metabolism in the liver and metabolism in the gut wall, absolute bioavailability is about 50%. Peak blood concentrations are attained within about 2 hours after an oral dose. This leads to lower bioavailability of Quetiapine fumarate also having bitter taste. So to improve its bioavailability and to mask the taste solid dispersion technique was used using different carriers like PEG 6000, & Poloxamer. Results of prepared taste masking sachets by solid dispersion technique of Quetiapine fumarate by Fusion method & kneading method were discussed which includes solubility, drug content uniformity, and in vitro dissolution studies. Characterization in solid state was done by FT-IR studies. Finally by comparing all the formulations i.e., F1-F12 containing Quetiapine fumarate, Poloxamer and PEG 6000 in different ratios, Invitro drug release of Quetiapine fumarate with PEG 6000 in 1:3 by Fusion method shows 98.62% drug release at the end of 60mins. By comparing the release kinetics studies of best formulation of Quetiapine fumarate with zero order and first order we can say that the best formulation follows Zero order release kinetics studies.